1997
DOI: 10.1002/(sici)1096-8628(19971112)72:4<403::aid-ajmg6>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Reference values for body proportions and body composition in adult women with Ullrich-Turner syndrome

Abstract: This cross sectional study was undertaken to establish reference values for adult women with Ullrich-Turner syndrome (UTS) verified cytogenetically by blood karyotyping and not treated with growth hormone during childhood and adolescence, with respect to anthropometric and body composition measurements, for future evaluations of growth promoting therapy. All members of the Danish Turner Association were invited, and 79 women with UTS participated. Forty-two had the 45,X karyotype and the other 37 had different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Furthermore, in our study, there is no statistical difference between the karyotype 45, X and the remaining karyotypes on any of the variables measured and this was compatible with the results of Gravholt et al [ 21 ]. Some of the karyotype subgroups in the study performed by Gravholt et al were too small for evaluation; therefore, they compared the karyotype 45, X with the rest of the karyotypes as in our study, and anthropometric proportions showed no statistical difference between groups [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, in our study, there is no statistical difference between the karyotype 45, X and the remaining karyotypes on any of the variables measured and this was compatible with the results of Gravholt et al [ 21 ]. Some of the karyotype subgroups in the study performed by Gravholt et al were too small for evaluation; therefore, they compared the karyotype 45, X with the rest of the karyotypes as in our study, and anthropometric proportions showed no statistical difference between groups [ 21 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study we found no significant differences in BMI and WHR depending on whether rGH therapy was applied or not. The same was observed by others [ 23 25 ]. In our own study the mean fat content was lower in group 1 than in group 2; the difference was statistically significant.…”
Section: Discussionsupporting
confidence: 90%
“…Women with TS have a higher body mass index and an increased hip-to-waist ratio, increased total and visceral fat mass, and decreased skeletal muscle mass compared to unaffected women [91,92]. Physical activity and fitness levels are also lower [32,93].…”
Section: Obesity and Physical Activitymentioning
confidence: 99%
“…Physical activity can help individuals to reduce their body weight and has a positive effect on BP [90] by reducing vascular resistance, increasing parasympathetic activity and decreasing psychosocial stress [91]. Women with TS have a higher body mass index and an increased hip-to-waist ratio, increased total and visceral fat mass, and decreased skeletal muscle mass compared to unaffected women [91,92]. Physical activity and fitness levels are also lower [32,93].…”
Section: Obesity and Physical Activitymentioning
confidence: 99%